The precarious employment in Tunisia - Gaied , Sirine (Journal of Human Sciences, 2023)
The main aim of this paper is to review the vocational integration and the insecurity of female employment in the Tunisian labor market. In the first part, we will be dealing with the evolving status of Tunisian women, including the decline of illiteracy and the improvement of their levels of educational attainment. In the second part, we will be analyzing the characteristics of unemployment and employment depending on several variables. We will have a particular focus on the informal employment and the precarious employment of women.